Improving the Learning Outcomes in Heat Source Materials Through the Application of Group Work Learning Models - Wa Malufia, Wa Malufia (International Journal of Management and Education in Human Development, 2021)
The goal to be achieved is the implementation of this learning improvement, namely to improve the learning achievement of students in class IV SDN 35 Kendari through a group work learning model . The benefits of this research are: (1)for teachers: by conducting classroom action research the teacher can find out the right method so that it can improve and improve the quality of the learning process in the classroom, so that problems faced by students and by the teacher can be minimized, (2) for students: can improve their learning outcomes in Science on the material of Heat Energy Sources, (3) for schools: classroom action research can provide good input for schools to improve the quality of the science learning process. Based on the results of the cycle I action test, it was found that the classical student learning outcomes of the subject matter were 50% or as many as 12 students who scored >65 with an average value of 66.41, while the results of the evaluation of the second cycle of action showed that the classical student learning outcomes of the subject matter were 95.83% or 23 students scored > 65 with an average value of 76.66. From the results of observation, evaluation and reflection in each action cycle, it can be concluded that through the application of the group work learning model it can improve student learning outcomes in the material of Heat Energy for fourth grade students of SD Negeri 35 Kendari.